PERHITUNGAN WAKTU OPTIMAL UNTUK MEMENUHI PRODUKSI PENGUPASAN LAPISAN OVERBURDEN MENGGUNAKAN ANALISIS REGRESI LINEAR BERGANDA - Vitri Rospitasari; Diana Purwandari; Aditya Budi Nugraha (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2022)
PT. Anugerah Starindo Sakti which focuses on mining, especially on desiccant mining, is located in Pamotan Village, Kalipucang District, Pangandaran Regency, West Java Province. Based on the overburden stripping production data at PT. Anugerah Starindo Sakti could not achieve the production target. After doing multiple linear regression analysis with the results 641,63=698,66-91,28X1-81,48X2 and assuming that when standby time and repair/breakdown time is worth 0, then the linear regression results are X2=-1,667X1+0,7with a maximum limit of 1.3 hours for standby time and repair/ breakdown time of 17.5 hours. Regression results that show a coefficient of determination of 0.98 and a correlation coefficient of 0.99 or which means the effect of loss time on the amount of production is 99%. Therefore, it is better to make improvements to the inhibiting factors (loss time), especially improvements to standby time and repair/breakdown time